100 x Photo : 100 Photographs from the Collection of the Stedelijk Museum Amsterdam. - Fuchs, Rudi H.; Visser, Hripsimé; Stedelijk Museum Amsterdam (Amsterdam Bussum : Thoth Publishers, 1996)
Het Stedelijk Museum toont vanaf 14 september honderd foto's uit zijn befaamde fotocollectie. De tentoonstelling laat verschillende thema's zien die belangrijk zijn in deze collectie - zoals erotiek, verlangen, dood - maar pint de fotografie niet vast op die onderwerpen zelf. The Stedelijk Museum's photography collection is the oldest of its kind in a European museum for modern art. It was established in 1958 during the directorship of Willem Sandberg and particularly since the 1970s, has grown into an internationally oriented collection of 20th century photography. This catalogue presents a selection of 100 photographs from the about 4000 in the Museum's holdings. Drawing on famous masterpieces and lesser known images, this selection gives an impression of the quality of the collection and of the versatility of photography's potential for expression over the past century, from Eugène Atget to Andreas Gurski and from Lewis Hine to Nan Goldin. In addition to an introduction outlining the history of the collection, there are short essays about the separate photographs and their makers. References for further reading, a list of photo exhibitions held at the Museum and an overview of all the photographers whose work is included in the collection make this book an essential reference source for specialists in the field and all lovers of photography.
Aarsman, Hans ; Abbott, Berenice ; Adams, Ansel ; Andriesse, Emmy ; Appelt, Dieter ; Araki, Nobuyoshi ; Arbus, Diane ; Atget, Eugène ; Avedon, Richard ; Baltz, Lewis ; Beaton, Cecil ; Bellmer, Hans ; Bellocq, Ernest James ; Bergmann-Michel, Ella ; Berssenbrugge, Henri ; Besnyö, Eva ; Bischof, Werner ; Blossfeldt, Karl ; Blumenfeld, Erwin ; Both, Katt ; Brandt, Bill ; Brassaï ; Capa, Robert ; Cartier-Bresson, Henri ; Clark, Larry ; Deroo, Wijnanda ; Dijkstra, Rineke ; Doisneau, Robert ; Eggleston, William ; van der Elsken, Ed ; Evans, Walker ; Feininger, T. Lux ; Fischli, Peter ; Frank, Robert ; Freed, Leonard ; Friedlander, Lee ; Gloeden, Wilhelm von ; Goldin, Nan ; Guermonprez, Paul ; Gursky, Andreas ; Hine, Lewis W. ; Hollós-Consemüller, Ruth ; Horsfield, Craigie ; Kaap, Gerald Van Der ; Kamman, Jan ; Käsebier, Gertrude ; Kertesz, André ; van der Keuken, Johan ; Klein, Aart ; Klein, William ; Koudelka, Josef ; Krims, Leslie R. ; Kruger, Dolf ; Kulik, Zofia ; Kuprianov, Vladimir ; Langdon Coburn, Alvin ; Loew, Heinz ; Longo, Robert ; Lyon, Danny ; Man Ray ; Mantz, Werner ; Mapplethorpe, Robert ; Michals, Duane ; van Moerkerken, Emiel ; Moholy, Lucia ; Moholy-Nagy, Laszlo ; Munkacsi, Martin ; Newman, Arnold ; Nixon, Nicholas ; de Nooijer, Paul ; Nothelfer, Gabriele ; Nothelfer, Helmut ; van Ojen, Evert M. ; Oorthuys, Cas ; Penn, Irving ; Peterhans, Walter ; Renger-Patzsch, Albert ; Ribeiro Salgado, Sebastiao ; Roh, Franz ; Salomon, Erich ; Sander, August ; Sannes, Sanne ; Schleifer, Fritz ; Schuitema, Paul ; Sert, José Maria ; Sherman, Cindy ; Shunk, Harry ; Slavin, Neal ; Smith, William Eugene ; Stieglitz, Alfred ; Stone, Sasha ; Strand, Paul ; Taconis, Krijn ; Tas, Henk ; Vishniac, Roman ; Weegee ; Weiss, David ; Wessing, Koen ; Weston, Edward Henry ; etc.
geboortedatum per kunstenaar
100 X Photo : 100 Photographs from the Collection of the Stedelijk Museum Amsterdam, 14.09.- 17.11.1996
Engels
boek